DOMESTIC VIOLENCE AS A CAUSE FOR DIVORCE: ARE THERE EFFORTS FOR MEDIATION? - Jasmaniar Jasmaniar; Sutiawati Sutiawati (Al-Bayyinah, 2020)
AbstractMediation as an alternative to dispute resolution has been integrated in court. Further provisions for mediation as a process that must be carried out are further regulated in the Supreme Court Regulation No. 1 of 2016 concerning mediation procedures in court. This means that cases filed in court including cases of divorce on the grounds of domestic violence are obliged to undergo mediation. This research is a normative legal research that focuses on solving legal problems by providing a basis for theoretical argumentation and adequate concepts. Sources of data in this study came from primary, secondary and tertiary legal materials. The findings of the study indicate that in cases of divorce on the grounds of domestic violence, they still take the path of mediation. This is stated in the Supreme Court Regulation No. 1 of 2016 which requires mediation in civil cases, even in the Supreme Court Regulation states that in the resolution of a civil case a judge does not take mediation, it is considered to have violated the law. Divorce cases on the grounds of domestic violence cannot be categorized as a criminal act, if the filing process is a civil process (divorce), it is different when the wife makes a complaint (complaint offense) and/or an ordinary offense which results in a violation of the Abolition of Domestic Violence. However, divorce cases are considered civil and processed according to other civil cases and on the grounds of domestic violence they still go through mediation. Keywords: Mediation; Divorce; Violence; Household.